A group of scs elements function as domain boundaries in an enhancer-blocking assay. - Kellum, R (1992)
Chromosomes of higher eukaryotes are thought to be organized into a series of discrete and topologically independent higher-order domains. In addition to providing a mechanism for chromatin compaction, these higher-order domains are thought to define independent units of gene activity. Implicit in most models for the folding of the chromatin fiber are special nucleoprotein structures, the domain boundaries, which serve to delimit each higher-order chromosomal domain. We have used an "enhancer-blocking assay" to test putative domain boundaries for boundary function in vivo. This assay is based on the notion that in delimiting independent units of gene activity, domain boundaries should be able to restrict the scope of activity of enhancer elements to genes which reside within the same domain. In this case, interposing a boundary between an enhancer and a promoter should block the action of the enhancer. In the experiments reported here, we have used the yolk protein-1 enhancer element and an hsp70 promoter:lacZ fusion gene to test putative boundary DNA segments for enhancer-blocking activity. We have found that several scs-like elements are capable of blocking the action of the yp-1 enhancer when placed between it and the hsp70 promoter. In contrast, a MAR/SAR DNA segment and another spacer DNA segment had no apparent effect on enhancer activity.